Antecedents and outcomes of emotions and satisfaction of guests in the Malaysian Peer-to-Peer accommodation sector - Ali, Laiba (2018)
The main aim of this study is to investigate antecedents of guests’ behavioral intentions in Peer to Peer (P2P) accommodation sector of Malaysia. This study has three specific objectives that are: 1) to determine the effect of physical environment, social environment and price fairness on guest emotions within P2P accommodation sector in Malaysia; 2) to determine the effect of physical environment, social environment and price fairness on guest satisfaction within P2P accommodation sector in Malaysia; and 3) to determine the effect of guest emotions and guest satisfaction on guest’s behavioral intentions within P2P accommodation sector in Malaysia. A quantitative analysis of these antecedents is provided in this study in the context of Malaysia, and questionnaires were used to collect data as a principal data collection method. Data was collected online from tourists/guests (local and international), who have stayed at P2P accommodation in Malaysia during the last 24 months. This study used the purposive sampling and multiple sampling approaches in order to make the sample more generalized. Based on Stimulus-Organism-Response model theory, hypothesized theoretical models for the present study was developed and analyzed. Firstly, descriptive statistics were used to determine the demographic characteristics of the sample among other P2P accommodation practices in Malaysia. Partial Least Square (PLS) Structural Equation Modeling (SEM) was used to test the eight hypotheses of this study under three objectives. The findings showed that three dimensions of the physical environment had a significant positive impact on guest emotions and satisfaction, social environment had a significant positive impact on guest satisfaction only and price fairness had a significant positive impact on guest emotions only. Both guest emotions and satisfaction had a significant positive impact on guest behavioral intentions. This study had made contributions in theoretical, practical, policy and methodology. The findings suggested that government should educate all the working bodies and stakeholders of P2P accommodation about the services and importance of this sector. This study has tested few antecedents of behavioral intentions in Malaysian P2P accommodation sector. Future studies can test other antecedents in different sectors and contexts.